2014
DOI: 10.4103/0976-9668.127328
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocutaneous nocardiosis caused by Nocardia otitidiscaviarum: A case report and review of literature

Abstract: Nocardia otitidiscaviarum is a rare clinical isolate of primary cutaneous infections. This report describes a case of lymphocutaneous nocardiosis caused by N. otitidiscaviarum. Analysis of 16S ribosomal RNA gene of the isolate and the type strain of N. otitidiscaviarum DSM 43242 showed 100% similarity. The partial gene sequence of 1439 bp was submitted to GenBank. (EU031786). The isolate was susceptible only to amikacin, minocycline, linezolid and resistant to remaining other routine anti-nocardial drugs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
12
0
4
Order By: Relevance
“…[13] Beaman et al described that only 10 cases from 347 patients infected by Nocardia in United States were identified as N otitidiscaviarum infection. [4] Similarly, Kageyama et al [14] reported that out of more than 303 pathogenic Nocardia strains isolated from nocardiosis patients in Japan from 1992 to 2001, only 14 were identified as N otitidiscaviarum .…”
Section: Discussionmentioning
confidence: 99%
“…[13] Beaman et al described that only 10 cases from 347 patients infected by Nocardia in United States were identified as N otitidiscaviarum infection. [4] Similarly, Kageyama et al [14] reported that out of more than 303 pathogenic Nocardia strains isolated from nocardiosis patients in Japan from 1992 to 2001, only 14 were identified as N otitidiscaviarum .…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Pale stained (or un-stained) grains are characteristic for infections due to Scedosporium boydii (formerly Pseudallescheria boydii), Scedosporium apiospermum (white grains), Acremonium spp., Fusarium spp., Neotestudina rosatii, Aspergillus nidulans, Aspergillus flavus as well as Microsporum ferrugineum and Microsporum audouinii. [33][34][35][36] Yellow-brown grains are typically for Nocardia brasiliensis, Nocardia otitidiscaviarum (formerly Nocardia caviae), 37 Actinomadura madurae and Streptomyces somaliensis.…”
Section: Pathogenesismentioning
confidence: 99%
“…Out of all Nocardia species, N asteroids , N farcinica , and N brasiliensis are the primary pathogens causing nocardiosis, while other species are rare or reported less frequently . N otitidiscaviarum rarely causes infection, and it was first recognized in samples taken from a Sumatran cavy or guinea pig with ear disease . It is usually less pathogenic than other species of Nocardia …”
Section: Introductionmentioning
confidence: 99%
“…2 Nocardia infection can be caused by various species, including N asteroides, N brasiliensis, N otitidiscaviarum, N cyriacigeorgica, and N farcinica. 3 Out of all Nocardia species, N asteroids, N farcinica, and N brasiliensis are the primary pathogens causing nocardiosis, while other species are rare or reported less frequently. 4 N otitidiscaviarum rarely causes infection, and it was first recognized in samples taken from a Sumatran cavy or guinea pig with ear disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation